The effect of different higher education fee policies on education: A comparison between England and Germany. Issue 2 (6th March 2017) - von Alberti-Alhtaybat, Larissa; Abdelrahman, Njlaa; Al-Htaybat, Khaldoon
Abstract : Purpose: Higher education (HE) sectors form an important part of societies and their economy, on which the members of a society depend for their individual and collective future benefit. The purpose of this paper is to discuss the perceptions of accounting academics on the introduction of HE tuition fees in both England and Germany, and how this policy has affected the everyday life of academics and students alike in each country. The respective funding and reform approach sets the context of this study. Design/methodology/approach: The study has adopted a qualitative methodology, analysing data collected through semi-structured interviews. Accounting academics discuss their perceptions of both policies in the respective context. Academics were focussed on as implementers of educational policies. Accounting academics were chosen due to their academic and professional background, changing academic position in the global market and their representative stance in the academic context. The data analysis took place through coding interview data. Findings: While England's fees have been increased several times over the past 15 years, few German federal states have introduced, and have already abolished the policy. Reasons as to why the outcomes are so radically different are discussed based on interviews with accounting academics, and the implications for future practice are that to be successful political support must be sustained regardless of the changing governments, and the HE sector itself must have strong champions supporting this policy. Furthermore, the effect of the respective tuition fee policy with regard to education is addressed, which suggests that English students have a broader education package expectation, while with regard to actual classroom education both German and English students have similar outlooks. A further issue is the different political and education contexts, the current state of affairs and the societal impact. Originality/value: This study is one of the few to compare directly the differing tuition fee policies and the educational implications of these policies of Germany and England. These two cases are an illustration that Germany and England are at the opposite ends of the reform spectrum and that academics experience different expectations due to such different fee policies.